A New Predisposing Factor for Postoperative Atrial Fibrillation: Tube Insertion Site - Apaydın, Zinar; Timur, Barış; Yazıcı, Batuhan; Gözaçık, Kübra; Akbaş, Anıl; Aksu, Timuçin; İyigün, Taner (The Thoracic and Cardiovascular Surgeon, 2024)
The aim of this study is to compare the insertion sites of drainage tubes placed in the left thorax after elective coronary artery bypass grafting (CABG) surgeries.Patients were divided into two groups based on the site of tube insertion into the left hemithorax: those with a tube inserted from the subxiphoid region and those with a tube inserted from the left intercostal region. Comparative analyses between these two groups and factor analyses contributing to the outcome were performed.There were no significant differences observed in terms of age, gender, height, and weight among patients undergoing coronary artery bypass surgery based on the site of drain placement. Twelve patients (5.2%) required re-drainage procedures, with five (41.7%) for pneumothorax and seven (58.3%) for pleural effusion. Atelectasis was absent in 144 patients (62.1%) while present in 88 patients (37.9%). The frequency of atrial fibrillation (AF) was significantly higher in the group with intercostal drains. Additionally, pain scale scores were significantly higher in patients with intercostal drains. Path analysis revealed that the visual pain scale value played a full mediating role in the effect of the drain site on AF.The statistically significant occurrence of pain and higher rates of postoperative AF in patients with intercostal tube placement are noteworthy. We believe that in patients undergoing elective coronary artery bypass surgery, the drain placed in the left hemithorax should be inserted from the subxiphoid region, if there are no contraindications.
Keywords: coronary artery bypass surgery; atrial fibrillation; drain; pain